A importância da literatura infanto juvenil no ensino fundamental menor - BASTOS, Terezinha (2024)
Reading is a fundamental element for the individuals construct their knowledge , emphasizing their curiosity by providing them with new experiences for their psychological maturation. To be able to form child reader is necessary that it has significant experience with the reading that should not occur under compulsion, but it is presented in a pleasant way , arousing the interest and pleasure in the subject reading , doing with that this dialogue with the text . In elementary school we can not lose focus of making kids readers because reading should be inserted in the child's life from his childhood through family and be continued in school . Thus, the school becomes one of the leading institutions promoting the encounter between the child and reading , literature and the work of Monteiro Lobato . Form reader should be one of the main prerogatives of the elementary schools , so this research investigated how is this training in relation to the works of Monteiro Lobato . This is a survey of theoretical and practical basis , seeking authors that support the theoretical discussion based on the reading and educating readers in school and in life, especially in relation to Lobato works for children . The literature works on the written language , this is depending on the reading ability of students , assuming they have passed the school institution . Thus begins the connection between literature and education, literature and the point of attachment between the child and the school and society that will promote and foster conditions to realize the circulation of literature , with the appreciation of education and school, evidencing the importance of the habit of reading for the training of citizens . With that intellectuals , journalists and teachers begin to produce books for the strengthening of a modern Brazil .